The Effects of Special Labor Legislation for Women - Witte, Edwin E. (Quarterly Journal of Economics, 1927)
The Effects of Special Labor Legislation for Women Edwin E. Witte Edwin E. Witte Wisconsin Legislative Reference Library Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 42, Issue 1, November 1927, Pages 153–164, https://doi.org/10.2307/1885370 Published: 01 November 1927